KONTRIBUSI BERAS SIGER DALAM POLA KONSUMSI PANGAN RUMAH TANGGA KONSUMEN BERAS SIGER DI PROVINSI LAMPUNG - Wuryaningsih Sayekti; Dyah Aring Hepiana Lestari; Raden Hanung Ismono (Politeknik Negeri Lampung, 2021)
The objective of this research were to investigate: (a) the consumption pattern of beras siger, (b) the household consumption pattern (Diserable Dietary Pattern /Pola Pangan Harapan /PPH), and (c) the contribution of beras siger to household energy adequacy of beras siger consumer. This research was conducted at Metro City, South Lampung Regency, and Tulang Bawang Regency used survey method. The research population was beras siger consumer of Mekar Sari Agroindustry (Metro), Siti Hawa Agroindustry (South Lampung), and Toga Sari (Tulang Bawang). There were 25 household, 19 household, and 30 household from Mekar Sari, Siti Hawa, and Toga Sari Agroindustry respectively were taken by quota sampling. Data collection were carried out on May – August 2016 by interview while food consumption data collected by recall method. The method of analysis in this research was descriptive statistic. The result showed that: (a) the average of beras siger consumption of beras siger consumer at Lampung Province was 228,38 gram/household/day, the buying frequency was twice per month, in general beras siger was used as substitute of main food, and beras siger consumer buying beras siger at the factory, (b) the energy consumption level of consumer beras siger household were on good category with Desirable Dietary Pattern (DDH) score : 73,02, and (c) the average contribution of beras siger to energy adequacy was 10,84 percent. Keyword: beras siger, consumption pattern, PPH